Mechanisms of acetylcholinesterase protection against sarin and soman by adenosine A1 receptor agonist N6-cyclopentyladenosine. (August 2018) - Beste, Ariana; Taylor, DeCarlos E.; Shih, Tsung-Ming; Thomas, Thaddeus P.
Graphical abstract: Highlights: We study mechanisms of acetylcholinesterase (AChE) protection against nerve agents (NAs) sarin and soman by N 6 -cyclopentyladensosine (CPA). A truncated molecular model approach and density functional theory is used. Thermodynamic data suggest that CPA can compete with the NAs for the active site of AChE. We find a strong interaction between CPA and NA-conjugated AChE. Our results show an affinity between CPA and unbound NA. Abstract: Organophosphorus nerve agents (NAs) irreversibly inhibit acetylcholinesterase (AChE), the enzyme responsible for breaking down the neurotransmitter acetylcholine (ACh). The over accumulation of ACh after NA exposure leads to cholinergic toxicity, seizure, and death. Current medical countermeasures effectively mitigate peripheral symptoms, however; the brain is often unprotected. Alternative acute treatment with the adenosine A1 receptor agonist N 6 -cyclopentyladensosine (CPA) has previously been demonstrated to prevent AChE inhibition as well as to suppress neuronal activity. The mechanism of AChE protection is unknown. To elucidate the feasibility of potential CPA-AChE interaction mechanisms, we applied a truncated molecular model approach and density functional theory. The candidate mechanisms studied are reversible enzyme inhibition, enzyme reactivation, and NA blocking prior to enzyme conjugation. Our thermodynamic data suggest that CPA can compete with the NAs sarin and soman for the active site of AChE, but may, in contrast to NAs, undergo back-reaction. We found a strong interaction between CPA and NA conjugated AChE, making enzyme reactivation unlikely but possibly allowing for CPA protection through the prevention of NA aging. The data also indicates that there is an affinity between CPA and unbound NAs. The results from this study support the hypothesis that CPA counters NA toxicity via multiple mechanisms and is a promising therapeutic strategy that warrants further development.